2021
DOI: 10.3389/fphys.2021.711798
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Arterial Oxygen Saturation and Lung Ultrasound B-Lines After Competitive Deep Breath-Hold Diving

Abstract: Breath-hold diving (freediving) is an underwater sport that is associated with elevated hydrostatic pressure, which has a compressive effect on the lungs that can lead to the development of pulmonary edema. Pulmonary edema reduces oxygen uptake and thereby the recovery from the hypoxia developed during freediving, and increases the risk of hypoxic syncope. We aimed to examine the efficacy of SpO2, via pulse-oximetry, as a tool to detect pulmonary edema by comparing it to lung ultrasound B-line measurements aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Auscultation may demonstrate rales or crackles. Pulse oximetry >95% within 30 minutes of surfacing has a negative predictive value of 100% for lung injury (29). Ultrasound may demonstrate lung comets and areas of atelectasis (30).…”
Section: Medical Issues In Breath-hold Divingmentioning
confidence: 99%
“…Auscultation may demonstrate rales or crackles. Pulse oximetry >95% within 30 minutes of surfacing has a negative predictive value of 100% for lung injury (29). Ultrasound may demonstrate lung comets and areas of atelectasis (30).…”
Section: Medical Issues In Breath-hold Divingmentioning
confidence: 99%
“…There is also evidence that barotrauma may be more common than reported. Patrician et al ( 2021 ) recently confirmed by ultrasound that remaining low SpO 2 after deep dives reflected lung fluid accumulation.…”
Section: Introductionmentioning
confidence: 97%
“…With this perspective, POCUS has been used to detect venous gas emboli traveling from peripheral circulation to the heart when resurfacing after self-contained underwater breathing apparatus (SCUBA) dives [9,10] and signs of pulmonary edema after breath-hold diving (BHD) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%